The factors influence travel intention among students UiTM Kota Bharu / Normarliana Faranadia Ismail, Nur Fatinah Sazlin Mohamad Zuki and Siti Nur Aishah Adnan - Ismail, Normarliana Faranadia; Mohamad Zuki, Nur Fatinah Sazlin; Adnan, Siti Nur Aishah (2018)
Malaysia economic growth were contributed by tourism which act as an important subsector. The most often spend more than other tourists is from student or young traveler. According to Lim, Ramli, Yusof, & Cheah (2015), a young people have low level of income but they have high interest and leisure time to explore new destination. Student traveler is usually raises with an environment with a wide and also will increase the range of travel opportunities. Based on the population statistics from Department of Statistics, Malaysia shows that there is 28.25 million of student or young traveler in Malaysia as in 2010. The main purpose of this study was conducted to identify the factors that influence travel intention among university students. In this study, data collection method that been used is survey questionnaire. Target population who is study in UiTM Kelantan Campus Kata Bharu. For finding sample size used the Raosoft application (Roasoft.Inc) to calculate the sample size with 95% confidence level. The questionnaire was distributed to 239 students in UiTM Kelantan Campus Kota Bharu which is 127 from Faculty Science Computer and Mathematics (FSKM) and 112 from Faculties in Business Management (BM) were selected. The data was analysed using statistical analysis software package (IBM SPSS). The method of analysis data is the multiple linear regression. This study has accomplished the several variables are significant. Based on the result of this study, destination image and budget are significant while travel time is not significant. Thus, the government, official tourism organisation and business leader should get prepared to unlock the power of young people in tourism market for the development of the country in the future.